The Most Suitable Office Chair Alternative For Drafting Studios: The Sample of Bartın University Landscape Architecture Department - İmren, Erol; İmren, Erol (My University, 2022)
In today’s drafting areas the design of interior elements in line with ergonomical criteria holds great importance from physiological and psychological aspects. Especially the chairs and desks, used by the students who spend most of their times in schools, should be designed in line with ergonomical criteria. In this study, a survey study was carried out with undergraduate students of Bartin University Landscape Architecture Department to determine their demands and requests on the issue. The AHP (Analytic Hierarchy Process) model was built in accordance with the user demands and requests, and accordingly the main and sub-factors of the model were determined as a means to make the most suitable chair selection for use in draft studios. According to the outcomes of AHP model, ergonomy (77%), economy (16%) and aesthetics (7%) were found to be the main effective factors in chair selection. Also, the chairs with adjustment function, armrest and lumbar support were determined as the most suitable ones for use in draft areas. In the results section of the study, the most suitable chair features for use in draft rooms, as well as suggestions for future studies are proposed.
Keywords: Mimarlık; Mühendislik; Makine; Malzeme Bilimleri; Tekstil; İstatistik ve Olasılık; Analytic Hierarchy Process (AHP); furniture industry; ergonomy; draft area; drawing chair